The Art Creation in the Traditional Art Area - Nimita, Esthi; Yundari, Mustika (PANGGUNG, 2017)
ABSTRACTThis article discusses the concept of creating a work of art within a traditional framework. Therefore we need to understand how a work of art was created in the context of tradition, and the difference with the creation of art in the modern world. This article also a discourse on what is actually called a traditional art, and the distiction between traditional art and modern art. In this case, the example is a tradisional dance of Java. The choice is in the hand of the artist, or an art connoisseur nevertheless, through a deeper understanding of the traditional arts and how it was created, so a person may have perspective about life, and the conjunction with God.Keywords:Art, Traditional Art, Modern Art, Creation Process, Flow, TaksuABSTRAKArtikel ini membahas konsep penciptaan suatu karya seni, dalam lingkup seni tradisional. Persoalan yang diangkat mengenai perlunya kita memahami bagaimana sebuah karya seni itu diciptakan dalam konteks tradisi, dan apa bedanya dengan penciptaan karya seni pada konteks modern, dengan pembahasan apa itu seni tradisional dan apa itu seni modern.Dalam hal ini, kebetulan yang dicontohkan adalah seni tari tari tradisi Jawa. Pilihan memang ada ditangan seniman atau penikmat seni,namun dengan memahami secara lebihdalam apa itu seni tradisional dan bagaimana karya seni tradisional itu diciptakan, maka seseorang dapat memiliki perspektif yang lebih baik mengenai hidup, kehidupan, dan hubungannya dengan Sang Pencipta.Kata Kunci:Seni, Seni Tradisional, Seni Modern, Proses Penciptaan, Flow, Taksu.Â